2003
DOI: 10.1111/j.1751-0813.2003.tb12887.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mycobacterium avium subsp paratuberculosis from environmental samples collected from farms before and after destocking sheep with paratuberculosis

Abstract: M a paratuberculosis can be detected by radiometric culture in environmental samples from farms grazed by sheep or goats with paratuberculosis. There is a relatively low likelihood of recovery of the organism from water samples from such farms, and at 5 or more months after removing stock with paratuberculosis the likelihood of positive cultures from environmental samples is very low. Although the analytical sensitivity of culture from environmental samples is less than that from faeces, surveys of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…On the other five farms, too few water samples were collected to enable a comparison with isolation rates from terrestrial sites. Water and sediment samples were also taken from a further 20 farms that had been destocked of Johne's disease-affected sheep for at least 11 months; there were several culture-positive samples, all of which were sediments from low-lying areas near dams or water courses (31). From these results, it can be assumed that low-lying and aquatic environments where feces accumulates may harbor M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other five farms, too few water samples were collected to enable a comparison with isolation rates from terrestrial sites. Water and sediment samples were also taken from a further 20 farms that had been destocked of Johne's disease-affected sheep for at least 11 months; there were several culture-positive samples, all of which were sediments from low-lying areas near dams or water courses (31). From these results, it can be assumed that low-lying and aquatic environments where feces accumulates may harbor M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis was isolated from ca. 20% of samples (31). On one farm, 17 water and sediment samples were collected, but only 1 of these was positive for M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…, bezoar (Capra aegagrus) (27) (Kopecna et al, 2006), chamois (Rupicapra rupicapra) (134) (Kopecna et al, 2006), hawk (1) (Florou et al, 2008), owl (1) (Florou et al, 2008), Spur-winged plover (1) (Nugent et al, 2011), wolf (1) (Florou et al, 2008), duck (1) (Whittington et al, 2003). M. paratuberculosis was cultured in all samples for Eurasian Otter (n=2) (Matos et al, 2013), Common snipe (1) (Corn et al, 2005), Tapir (1), Okapi (1), Gayal (1), Blesbok (3), Banteng…”
mentioning
confidence: 99%
“…At present there is no direct evidence of mycobacaterial adsorption to clay particles, although one study reported recovery of only 3.5% of non-tuberculous mycobacteria inoculated into soil samples and attributed this to adsorption (Brooks et al, 1984). Whittington et al (2003) inferred a similar phenomenon for MAP, but further studies are required to substantiate this.…”
Section: Discussionmentioning
confidence: 95%